2012
DOI: 10.1136/postgradmedj-2012-130851
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its selected determinants among urban adult women in South Delhi, India

Abstract: The high prevalence of metabolic syndrome among women of lower socioeconomic status is a cause of concern, and calls for an effective public health response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…The high prevalence of metabolic syndrome among populations of lower socioeconomic status is a cause of concern and calls for an effective public health response (13). Previous studies have confirmed higher mortality and lower life expectancy for Roma than for non-Roma (14).…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of metabolic syndrome among populations of lower socioeconomic status is a cause of concern and calls for an effective public health response (13). Previous studies have confirmed higher mortality and lower life expectancy for Roma than for non-Roma (14).…”
Section: Introductionmentioning
confidence: 99%
“…21 Sinha et al found 30% prevalence on 300 females from South Delhi. 24 Deshmukh et al reported prevalence of MS for 18% and 17% for males and females respectively in rural Wardha, Sewagram. 25 Sarkar et al found 30-50% prevalence in a study conducted on 305 adult Bhutias in sub-Himalayan areas.…”
Section: 4mentioning
confidence: 98%
“…Metabolic syndrome (MetS), also known as syndrome X, Insulin resistance, etc. in the literature, is really not a single disease but a constellation of cardiovascular disease risk factors and is now considered as a major worldwide public health problem (1). MetS is a collection of cardiometabolic risk factors that includes abdominal obesity, impaired fasting glucose level, and hypertension and is also related to certain lipid disturbances, including low levels of HDL, high fasting and postprandial levels of triglyceride -rich lipoproteins [mainly VLDL], and increased levels of small, dense LDL particles all of which increase the risk of cardiovascular disease incidence and mortality.…”
Section: Introductionmentioning
confidence: 99%